2011
DOI: 10.1111/j.1537-2995.2011.03388.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro quality of single‐donor platelets treated with riboflavin and ultraviolet light and stored in platelet storage medium for up to 8 days

Abstract: Mirasol treatment of PLTs followed by storage in PSM results in increased PLT activation and metabolism to a level similar to that reported for PLTs treated and stored in plasma. Units treated at a low volume (<150 mL) showed poor in vitro quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 40 publications
7
41
0
Order By: Relevance
“…In addition, a comparison of two PASs showed that phosphate helps maintain the pH in Mirasol-treated PLT concentrates. 26 In contrast, the elevated CD62P expression seems to be initiated by a different pathway that is more directly targeted by the Mirasol procedure. Despite the fact that a rise in CD62P expression and annexin A5 binding are almost always seen together, in our study we find a decoupling of the two processes, which has been described recently in vitro using different stimuli.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, a comparison of two PASs showed that phosphate helps maintain the pH in Mirasol-treated PLT concentrates. 26 In contrast, the elevated CD62P expression seems to be initiated by a different pathway that is more directly targeted by the Mirasol procedure. Despite the fact that a rise in CD62P expression and annexin A5 binding are almost always seen together, in our study we find a decoupling of the two processes, which has been described recently in vitro using different stimuli.…”
Section: Discussionmentioning
confidence: 91%
“…Cookson et al observed mean losses of 11% FV and 33% FVIII activities relative to baseline values and lesser declines of FII, FVII, FIX, and FXII after 144 hours of refrigerated storage of thawed FP made from whole blood held at room temperature for 24 hours. These factor losses failed to affect thrombin generation and produced only marginal lengthening of clot time, but no change in clot strength, in viscoelastic testing [77]. …”
Section: Overview: Assessing the Quality Of Transfusable Plasmamentioning
confidence: 99%
“…Although platelet activation by Mirasol treatment has been observed, the biological effect of this activation did not lead to acute lung injury [18, 27]. However, a recent work suggests that platelet transfusion clinical effectiveness might be reduced due to decreased normal platelet function after PRT procedures [28].…”
Section: Discussionmentioning
confidence: 99%